Prenatal Diagnosis of Chromosomal Mosaicism in Over 18,000 Pregnancies: A Five-Year Single-Tertiary-Center Retrospective Analysis - Li, Shuyuan; Shi, Yiru; Han, Xu; Chen, Yiyao; Shen, Yinghua; Hu, Wenjing; Zhao, Xinrong; Wang, Yanlin (Frontiers in Genetics, 2022)
Background: Chromosomal mosaicism (CM) is a common biological phenomenon observed in humans. It is one of the main challenges in prenatal diagnosis due to uncertain outcomes, especially when fetal ultrasonographic features appear normal. This study aimed to assess the phenotypic features of CM detected during prenatal diagnosis and the risk factors affecting parents’ pregnancy decisions. Materials and methods: A retrospective cohort study involving 18,374 consecutive pregnancies that underwent prenatal diagnosis by karyotyping, fluorescence in situ hybridization (FISH), or chromosome microarray analysis (CMA) was conducted. The association of risk factors with malformations detected by ultrasound and pregnancy outcomes were assessed using the chi-square test and binary logistic regression. Discordant results between the different methods were identified and further analyzed. Results: During this five-year period, 118 (0.6%) patients were diagnosed with CM. The incidence of CM in the chorionic villus, amniotic fluid, and umbilical cord blood was 3.2, 0.5, and 0.7%, respectively. The frequency of ultrasound malformations in individuals with a high fraction of autosomal CM was significantly higher than that in other groups (62.5% vs. 21.4-33.3%, all P <0.05). Inconsistent results between karyotyping and CMA/FISH were observed in 23 cases (19.5%). The risk of pregnancy termination in cases with ultrasound malformations, consistent results, autosomal CM, or a high CM fraction increased with an odds ratio of 3.09, 8.35, 2.30, and 7.62 (all P <0.05). Multiple regression analysis revealed that all four factors were independent risk factors for the termination of pregnancy. Conclusion: Patients with a high fraction of autosomal CM are more likely to have ultrasound malformations. Inconsistent results between different methods in CM are not rare. Ultrasound malformations, consistent results between different methods, autosomal CM, and a high CM fraction were independent risk factors for the choice to terminate pregnancies..